2016
DOI: 10.1128/aem.01829-16
|View full text |Cite
|
Sign up to set email alerts
|

The Riemerella anatipestifer AS87_01735 Gene Encodes Nicotinamidase PncA, an Important Virulence Factor

Abstract: Riemerella anatipestifer is a major bacterial pathogen that causes septicemic and exudative diseases in domestic ducks. In our previous study, we found that deletion of the AS87_01735 gene significantly decreased the bacterial virulence of R. anatipestifer strain Yb2 (mutant RA625). The AS87_01735 gene was predicted to encode a nicotinamidase (PncA), a key enzyme that catalyzes the conversion of nicotinamide to nicotinic acid, which is an important reaction in the NAD ؉ salvage pathway. In this study, the AS87… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Other already described nicotinamidases are distributed in different clades throughout the phylogenetic tree, including a clade for yeasts ( Fig 2 , yellow) and nematodes ( Fig 2 , blue), where Saccharomyces cerevisiae and Caenorhabditis elegans nicotinamidases are included [ 18 , 24 , 26 , 28 , 29 , 56 ], respectively. The nicotinamidases from pathogenic microorganisms are distributed in three different clades, one including those of Borrelia burgdorferi , Leishmania infantum , Acinetobacter baumanii and the recently described nicotinamidase from Riemerella anatipestifer [ 4 6 , 18 , 20 ] ( Fig 2 , orange); and the others containing those of Mycobacterium tuberculosis [ 31 33 ] ( Fig 2 , red), and Streptococcus pneumoniae [ 18 , 34 ] ( Fig 2 , purple), respectively. Finally, it is worth mentioning that the clade described by Plasmodium falciparum nicotinamidase [ 18 ] and related members of the Plasmodium genus represented an special case in the phylogenetic tree ( Fig 2 , pink), since their sequences are longer than those of the rest of nicotinamidases, showing an N-ter extension of about 200 amino acids of unknown function.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other already described nicotinamidases are distributed in different clades throughout the phylogenetic tree, including a clade for yeasts ( Fig 2 , yellow) and nematodes ( Fig 2 , blue), where Saccharomyces cerevisiae and Caenorhabditis elegans nicotinamidases are included [ 18 , 24 , 26 , 28 , 29 , 56 ], respectively. The nicotinamidases from pathogenic microorganisms are distributed in three different clades, one including those of Borrelia burgdorferi , Leishmania infantum , Acinetobacter baumanii and the recently described nicotinamidase from Riemerella anatipestifer [ 4 6 , 18 , 20 ] ( Fig 2 , orange); and the others containing those of Mycobacterium tuberculosis [ 31 33 ] ( Fig 2 , red), and Streptococcus pneumoniae [ 18 , 34 ] ( Fig 2 , purple), respectively. Finally, it is worth mentioning that the clade described by Plasmodium falciparum nicotinamidase [ 18 ] and related members of the Plasmodium genus represented an special case in the phylogenetic tree ( Fig 2 , pink), since their sequences are longer than those of the rest of nicotinamidases, showing an N-ter extension of about 200 amino acids of unknown function.…”
Section: Resultsmentioning
confidence: 99%
“…However, human and mammalian genomes do not encode nicotinamidases and convert NAM directly into nicotinamide mononucleotide (NMN), which is then adenylated back to NAD + in a step catalyzed by NMN adenylyltransferase (EC 2.7.7.1). This absence of nicotinamidase activity in humans and its crucial role in the NAD + salvage pathways of not only the human pathogens involved in Lyme disease [ 4 ] and infantile visceral leishmaniasis [ 5 ], but also in an epizootic disease of domestic ducks caused by Riemerella anatipestifer [ 6 ], makes this enzyme a promising drug target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virulence determinants of Bergeyella species are incompletely understood and are an emerging area of research. Recently, pncA , which encodes a nicotinamidase in the related species R. anatipestifer, was identified as an important virulence factor and determinant of invasive cardiac disease in animal models [11]. We identified a related nicotinamidase gene with 71% nucleotide similarity; it is possible that this gene also serves as a key virulence determinant in B. cardium .…”
Section: Discussionmentioning
confidence: 99%
“…Several virulence factors of R . anatipestifer have been identified, including VapD 5 , CAMP cohemolysin 6 , outer membrane protein A 7 , putative genes associated with lipopolysaccharide (LPS) synthesis 8 10 and nicotinamidase 11 . In our previous study, 49 virulence-associated genes were identified by transponson mutagenesis.…”
Section: Introductionmentioning
confidence: 99%